Emerging two-dimensional materials-enabled diagnosis and treatments of Alzheimer's disease: Status and future challenges. (June 2021) - Song, Shiting; Wu, Jingwen; Cheng, Ying; Ma, Lixiang; Liu, Tao; Liu, Jia; Liu, Jun; Sotor, Jaroslaw; Luan, Ping
Highlights: Eliminating aβ peptides aggregates and preventing or interfering with aβ peptides aggregation are the two main treatment strategies for AD. Transforming the β-sheet structure of aβ aggregates into harmless structures is an effective strategy for the treatment of AD. Graphene oxide is widely used to detect AD biomarkers, including aβ proteins and tau proteins, AChE, miRNAs and S100ß. GO, BP, g-C3 N4, fullerene C60 and other 2D materials treat AD with photodynamic and photothermal effects. Abstract: Two-dimensional (2D) nanomaterials have been widely used in pharmaceutical applications due to their advantages of higher drug loading, controllable drug release, high stability, biodegradability, biocompatibility, and generally lower toxicity. This review presents state-of-the-art advancement in the context of utilizing 2D nanomaterials for the diagnosis and treatment of Alzheimer's disease (AD). The core pathological features of AD include amyloid plaques formed by amyloid beta protein (Aβ) aggregation in the cerebral cortex and hippocampus, and the self-assemble of Aβ peptides into β-sheet-rich aggregates. Early and accurate detection of AD biomarkers provide potential means for its diagnosis and treatment. Studies have indicated that 2D nanomaterials can significantly improve the detection accuracy and specificity of AD biomarkers (such as Aβ protein, tau protein, acetylcholinesterase (AChE), Acetylcholine (ACh), MicroRNAs, and S100β protein). In the treatment of AD, inhibiting the aggregation of Aβ and transforming the β-sheet structure of Aβ aggregates into harmless structures has been proved to be the effective strategies. 2D nanomaterials have application potential in the treatment of AD because they can degrade Aβ peptides or inhibit Aβ peptide aggregation through photodynamic or photothermal effects. However, most of the in vivo cytotoxicity mediated by nanomaterials has not yet been resolved.